The Impact of Ageing on 11C-Hydroxyephedrine Uptake in the Rat Heart - Werner, Rudolf A. (Sci Rep, 2018)
We aimed to explore the impact of ageing on 11C-hydroxyephedrine (11C-HED) uptake in the healthy rat heart in a longitudinal setting. To investigate a potential cold mass effect, the influence of specific activity on cardiac 11C-HED uptake was evaluated: 11C-HED was synthesized by N-methylation of (−)-metaraminol as the free base (radiochemical purity >95%) and a wide range of specific activities (0.2–141.9 GBq/μmol) were prepared. (11)C-HED (48.7 ± 9.7MBq, ranged 0.2–60.4 μg/kg cold mass) was injected in healthy Wistar Rats. Dynamic 23-frame PET images were obtained over 30 min. Time activity curves were generated for the blood input function and myocardial tissue. Cardiac 11C-HED retention index (%/min) was calculated as myocardial tissue activity at 20–30 min divided by the integral of the blood activity curves. Additionally, the impact of ageing on myocardial 11C-HED uptake was investigated longitudinally by PET studies at different ages of healthy Wistar Rats. A dose-dependent reduction of cardiac 11C-HED uptake was observed: The estimated retention index as a marker of norepinephrine function decreased at a lower specific activity (higher amount of cold mass). This observed high affinity of 11C-HED to the neural norepinephrine transporter triggered a subsequent study: In a longitudinal setting, the 11C-HED retention index decreased with increasing age. An age-related decline of cardiac sympathetic innervation could be demonstrated. The herein observed cold mass effect might increase in succeeding scans and therefore, 11C-HED microPET studies should be planned with extreme caution if one single radiosynthesis is scheduled for multiple animals.